2013
DOI: 10.1603/me12056
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal and Cytotoxic Activities of Extracts From 11 Native Plants From Northeastern Mexico

Abstract: Of all mosquito-borne viral diseases, dengue is spreading most rapidly worldwide. Conventional chemical insecticides (e.g., organophosphates and carbamates) effectively kill mosquitoes at their larval stage, but are toxic to humans. Natural product-based insecticides may be highly specific. Herein, we report the insecticidal activities of 11 native Mexican plants against Aedes aegypti (L). Ether extracts of Ambrosia confertiflora De Candolle, Thymus vulgaris (L.), and Zanthoxylum fagara (L.), and both ether an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, cellular death and loss of function may result from disturbed proton motive force and decreased membrane permeability [23] . The extract from Coccinia grandis leaves may target a variety of proteins, including structural proteins, ion channels, signalling molecules, enzymes, receptors, and bio membranes, among other cellular constituents [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cellular death and loss of function may result from disturbed proton motive force and decreased membrane permeability [23] . The extract from Coccinia grandis leaves may target a variety of proteins, including structural proteins, ion channels, signalling molecules, enzymes, receptors, and bio membranes, among other cellular constituents [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the inhibitory effect of the methanolic extract of Z. fagara on glucose absorption may explain its antihyperglycemic effect in in vivo. To date, for Z. fagara, only larvicidal activity has been reported (17); however, several species of the genus Zanthoxylum have been reported as inhibitors of digestive enzymes (18,19) and as antidiabetics (20). Silva et al (21) reported the antiviral activity of hydroalcoholic extract of J. dioica, while Araujo et al (22) showed that the aqueous extract of J. dioica is neither cytotoxic nor genotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…perniciosum showed the lowest larvicidal activities, with LC 50 values of, 80, 50, and 20 µg/mL, respectively [51]. Other organic extracts observed to have larvicidal activity against A. aegypti include those of R. chalepensis , T. vulgaris , and Z. fagara , exhibiting notable LC 50 values of 1.8, 4.4 and 75.1 µg/mL, respectively [52]. In contrast, the aqueous extract of A. indica showed slight effects towards four different instars of C. quinquefasciatus (LD 50 = 410–550 ppm) [53].…”
Section: Insecticidal Compounds and Plant Extractsmentioning
confidence: 99%